2020
DOI: 10.3390/diseases8040040
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Myocardial Injury in COVID-19-Infected Patients: A Systematic Review and Meta-Analysis

Abstract: Introduction: The incidence of acute myocardial injury (AMI) among Coronavirus Disease 19 (COVID-19)-infected patients remain unclear. We aimed to conduct a systematic review and meta-analysis to further explore the incidence AMI in these patients. Methods: We comprehensively searched the MEDLINE, EMBASE and Cochrane databases from their inception to August 2020. The included studies were prospective or retrospective cohort studies that reported the event rate of AMI in COVID-19 patients. Data from each study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 44 publications
(11 reference statements)
1
32
1
2
Order By: Relevance
“…COVID-19 is a multi-systemic disease, which may occur with complications at presentation or developing during the acute phase of illness. These complications may be respiratory, 40 cardiovascular, [41][42][43][44][45] renal, [46][47][48] gastrohepatic, [49][50][51][52][53] thromboembolic, [54][55][56][57][58] neurological, 59-61 cerebrovascular [62][63][64] and autoimmune 13,65 among others.…”
Section: Complications Associated With Long Covid-19mentioning
confidence: 99%
“…COVID-19 is a multi-systemic disease, which may occur with complications at presentation or developing during the acute phase of illness. These complications may be respiratory, 40 cardiovascular, [41][42][43][44][45] renal, [46][47][48] gastrohepatic, [49][50][51][52][53] thromboembolic, [54][55][56][57][58] neurological, 59-61 cerebrovascular [62][63][64] and autoimmune 13,65 among others.…”
Section: Complications Associated With Long Covid-19mentioning
confidence: 99%
“…Several systematic reviews and meta-analyses have reported their findings on ACI in COVID-19 patients (Table 1). 4,[20][21][22][23][24][25][26][27][28][29][30] A systematic review of 8 studies comprising 1,229 patients showed that the frequency of ACI was 16% (95% CI: 9%-27%), albeit with high (93%) heterogeneity among the studies. 4 A metaanalysis of 16 studies comprising 2224 patients indicated that the incidence of ACI was 24.4% in hospitalized COVID-19 patients.…”
Section: Acute Cardiac Injury (Aci)mentioning
confidence: 99%
“…37 In addition, advanced age, coagulopathy, acute respiratory distress syndrome (ARDS), and other comorbidities are associated with increased risk of in-hospital mortality in COVID-19 patients with ACI. 30,38 Pre-existence of heart failure and hypertension, and high cardiac biomarkers correlate with worse outcomes. 29…”
Section: Myocardial Injury In Covid-19mentioning
confidence: 99%
“…Different works of the literature showed that there is a strong correlation between acute myocardial Injury and COVID-19 infection. New studies are being published from around the globe but the link between acute myocardial injury and COVID-19, the prevalence, reliability of diagnostic modalities, independent predictors, and clinical outcomes are still uncertain and a topic of debate [ 22 , 24 , 26 , [32] , [33] , [34] , [35] , 41 , 44 , 50 , 53 , [57] , [58] , [59] , 62 , 76 , [81] , [82] , [83] , [84] , [85] ].…”
Section: Discussionmentioning
confidence: 99%
“…Our meta-analysis revealed that the pooled prevalence of acute myocardial injury in patients with COVID-19 was 22.33 (95 % CI: 17.86 to 26.81) which is relatively higher than other meta-analyses by Prasitlumkum et al and Alzahrani et al, 20.0 % (95 % CI 16.1–23.8 %) and 20.62 respectively. This discrepancy might be related with inclusion of few studies and study setting where these authors included studies conducted mainly in china with Twenty-seven and nine studies respectively [ 81 , 83 ]. However, a meta-analysis by Zou et al including sixteen studies where fourteen of them were from China showed higher incidence of acute myocardial infarction (24.4 %) among COVID-19 patients [ 90 ].…”
Section: Discussionmentioning
confidence: 99%